Investigation the behaviors of vibrations waves from high-speed train modelling - Suvisit Banyam; Amphon Jarasjarungkiat; Boonyakorn Warawas (My University, 2021)
Railway transportation is important for public transportation in Thailand like Bangkok Mass Transit System (BTS) and Mass Rapid Transit (MRT). Therefore, the organization of national development has objective to develop in railway transportation. Moreover, they are planning to build railway in Thailand to connect between ASEAN and China. There are many researchers who studied about the railway transportation infrastructure by using various methods. However, in this studies, waves of high-speed train were investigated by using different velocities into force and free vibration equations from structural dynamic. Then the results showed that shorter range was happened due to the vibration waves of high-speed trains than waves of low-speed ones. Finally, finite element software was used to get characteristics of the waves. The results proved that the vibrations waves were strong at first 1-5meter, however, at the distances of 5-15meter waves were decreased significantly in intensity. It was reduced to the end or there was no effect at the distance more than 18meter waves from the wave source.
Keywords: High speed train; Railway Engineering and Dynamics